2018
DOI: 10.4314/jab.v121i1.4
|View full text |Cite
|
Sign up to set email alerts
|

Contrôle des germes endogènes par usage d’agents antimicrobiens et réponse de différents explants durant la phase d’initiation <i>in vitro</i> de l'ananas (<i>Ananas comosus</i> (L.) Mill var. comosus)

Abstract: Contrôle des germes endogènes par usage d'agents antimicrobiens et réponse de différents explants durant la phase d'initiation in vitro de l'ananas (Ananas comosus (L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…It is therefore necessary to use sterile materials. Some studies have shown that the surface disinfection usually done during in vitro culture does not effectively eliminate infections, especially bacterial infections which are endogenous and appear gradually during culture [32,33,34,35]. Thus, antimicrobial agents (bactericides and / or fungicides) are sometimes added to the culture medium in order to eliminate germs or prevent their expression [36,35].…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore necessary to use sterile materials. Some studies have shown that the surface disinfection usually done during in vitro culture does not effectively eliminate infections, especially bacterial infections which are endogenous and appear gradually during culture [32,33,34,35]. Thus, antimicrobial agents (bactericides and / or fungicides) are sometimes added to the culture medium in order to eliminate germs or prevent their expression [36,35].…”
Section: Discussionmentioning
confidence: 99%
“…Also, a generalized linear model was applied to determine the influence of growth regulators on the leaves number, roots number, leaves length, and stem height for each cultivar during the five weeks of culture. Analysis of variance (ANOVA) was performed to determine significant difference among category of explants regeneration using Newman and Keuls test at the 5% threshold [21].…”
Section: Experimental Design and Data Analysismentioning
confidence: 99%
“…The explants in the positions out of 3 were not established yet. Thus, the position of buds in other species like pineapple [21] have been shown very influencing plantlets regeneration. It is also reported a high correlation between the type of explants, its positions, and the type of growth regulators used for plantlets regeneration [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, micropropagation is a valid and reliable method for the large-scale propagation of plant species [19] and can be initiated from various organs [20][21][22]. However, its success depends mainly on the plant disinfection process [23], which allows the elimination of pathogens before seeding [24]. In addition, the success of in vitro culture depends on the species, cultivar, tissue type, composition of the culture medium, and age of the cultured organ [25,26].…”
Section: Introductionmentioning
confidence: 99%